PENGARUH MEDIA ULAR TANGGA BERBASIS MISI TERHADAP HASIL BELAJAR PKN SISWA SDI BANI HASYIM - Ulmy, Adella Yauma; Saharani, Adelia; Afrizal, Afrizal; Ertanti, Devi Wahyu (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The lack of engaging learning media in Civics Education (PKn) often results in low student achievement at the elementary level. This study aims to examine the influence of a mission-based snakes and ladders game as an instructional medium on the learning outcomes of fourth-grade students at SDI Bani Hasyim. A pre-experimental method with a one-group pretest-posttest design was employed. The research involved 20 students selected through total sampling. Data were collected using written tests administered before and after the learning intervention. The results showed an increase in the average score from 75.4 (pretest) to 88.5 (posttest), with 100% of students meeting the minimum mastery criteria. Additionally, the use of this game-based medium enhanced student participation during the learning process. These findings suggest that mission-based educational games have the potential to support improved learning outcomes in Civics Education, although further research is needed to validate their effectiveness in broader contexts